THE MORAL VIEWS ON PUBLIC ADMINISTRATION AND LEADERSHIP IN NIZAMULMULK’S “THE POLICY” - Kamolov, Dostonbek (Journal of Contemporary World Studies, 2024)
The article discusses the ethical views on public administration in Nizamulmulk's “the policy”, the moral qualities imposed on the King, ministers, and common servants, and considerations on public administration.